The Scholarship of Practice and Stewardship of Higher Education. Issue 178 (June 2017) - Braxton, John M.; Ream, Todd C.
Abstract : This chapter describes the enactment of three levels of a scholarship of practice for higher education. The stewardship played by each of these levels constitutes the central focus of this chapter.